PENGARUH KECEMASAN FINANSIAL, LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF - Rini Windiyani; Idham Lakoni; Eko Wediyanto (Yayasan Insani Mandiri Santani, 2026)
This study aims to determine the influence of financial anxiety, financial literacy, and lifestyle on the consumptive online shopping behavior of Shopee PayLater users among students in Bengkulu City. The increasing phenomenon of Buy Now Pay Later (BNPL) service usage among students has encouraged consumptive behavior due to easy access to digital credit, modern lifestyles, and poor financial management. This research employed a quantitative approach using an associative method. The population in this study consisted of students in Bengkulu City who use Shopee PayLater. The sampling techniques used were purposive sampling and snowball sampling, with a total sample of 150 respondents. Data were collected through questionnaires using a Likert scale and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the assistance of SmartPLS version 4 software.The results of this study indicate that financial anxiety has a positive and significant effect on the consumptive online shopping behavior of Shopee PayLater users. Financial literacy has a negative and significant effect on consumptive behavior, meaning that the higher the level of financial literacy, the lower the students’ consumptive behavior. Lifestyle also has a positive and significant effect on the consumptive online shopping behavior of Shopee PayLater users. Simultaneously, financial anxiety, financial literacy, and lifestyle significantly influence the consumptive online shopping behavior of Shopee PayLater users among students in Bengkulu City. This study is expected to contribute to the development of financial management knowledge and serve as a consideration for students to be wiser in using digital financial services. Keywords: Financial Anxiety, Financial Literacy, Lifestyle, Consumptive Behavior, Shopee PayLater